Estimation of breeding values of Kankrej bulls under associated herd progeny testing program - SINGH, UMESH; RAJA, T V; RATHOD, B S; HPANCHASARA, H; ALYETHODI, R R (The Indian Journal of Animal Sciences, 2020)
A study was conducted to predict the expected breeding values of 8 Kankrej bulls inducted under the All India Coordinated Research Project on Cattle. A total of 127 first lactation 305-days records of Kankrej daughters born during the period between 2013 and 2017 were analyzed by Best Linear Unbiased Prediction (BLUP) method using Model VIII of LSMLMW software. The BLUP model included the Herd-year-season effect as fixed factor and sires as random factor. The overall average expected breeding value (EBV) was 2004.314 kg. The breeding values of Kankrej bulls ranged between - 151.321 and +189.733 kg. The results of the study revealed that the BLUP method discriminated the sires for their breeding values to a larger extent so that the genetically superior bulls can be discriminated from the poor bulls. Based on the results it was recommended only to use the frozen semen doses of two Gir bulls, viz. K020 and K017 to breed the Kankrej cows for increasing the milk production in subsequent generations.